Epidemiology of burns at the University Clinical Center in Gdańsk in 2017–2022 - Filip Lachowski; Paulina Bernecka; Agnieszka Pruska; Dominika Ossowska; Ada Łątkowska; Agata Błażyńska-Spychalska; Jerzy Jankau (Burns Open, 2023)
Introduction: The epidemiological trends in burns vary in different regions of the world.There are only few population-based reports on this topic in Poland.The aim of this study is to analyze statistics and epidemiology of burn patients. This can create a basis for improving the prevention of burns and their treatment. Methods: This retrospective study analysis the data of burn patients admitted to the University Clinical Center in Gdańsk from 2017 to 2022. Patients were included if their primary or secondary diagnosis was burn, according to ICD. A descriptive statistics were used to describe demographics, injury and management. Results: 584 patients were included in the study. The dominant age group were patients aged 20–29 (139–23,8%), followed by patients aged 30–39 (118–20,2%) and 40–49 (100–17,1%). Men accounted for 338 cases (57,9%), women for 246 (42,1%). The most numerous were burns of thermal etiology (391–67%), followed by chemical burns (172–29,3%). Among thermal burns, scalds and flames were responsible for 297 cases. Head was the most common burn location (281–48,1%), followed by the upper limb (263–45%). It varied depending on gender. Among 355 burn cases characterized with the degree of the burn, second-degree burns were the largest group − 197 cases (60,6%). Plastic, ophthalmological and laryngological consultations are the most frequently ordered type in the Hospital Emergency Department. 163 burn patients required hospitalization. Conclusions: The results obtained in our study are consistent with those of burn victims in other international studies in this field. It is crucial to conduct further epidemiological analysis to better quantify the impact of burns in Poland and to improve the treatment of burn patients.